2015
DOI: 10.1007/s00204-015-1495-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activation of furan moiety makes Diosbulbin B hepatotoxic

Abstract: Diosbulbin B (DIOB), a furanoid, is a major constituent of herbal medicine Dioscorea bulbifera L. Exposure to DIOB caused liver injury in humans and experimental animals. The mechanisms of DIOB-induced hepatotoxicities remain unknown. The present study demonstrated that DIOB induced hepatotoxicities in a time- and dose-dependent manner in mice. H&E stained histopathologic image showed the occurrence of necrosis in the liver obtained from the mice treated with DIOB at dose of 200 mg/kg. Pretreatment with KTC pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…The present study characterized the chemical identities of protein adducts resulting from the metabolic activation of DIOB both in vitro and in vivo. cis -Enedial 2 was identified as the reactive intermediate possibly associated with DIOB-induced hepatotoxicity [ 16 , 21 ]. The toxicity is likely triggered by protein covalent binding derived from the reactive metabolite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study characterized the chemical identities of protein adducts resulting from the metabolic activation of DIOB both in vitro and in vivo. cis -Enedial 2 was identified as the reactive intermediate possibly associated with DIOB-induced hepatotoxicity [ 16 , 21 ]. The toxicity is likely triggered by protein covalent binding derived from the reactive metabolite.…”
Section: Discussionmentioning
confidence: 99%
“…The adduction reached the peak at 12 h after the administration of DIOB. Our recent study demonstrated that the elevation of serum ALT reached the peak at 36 h in mice after a single dose of DIOB [ 16 ]. This indicates that a significant lag time between protein modification and the development of hepatotoxicity is required for the induction of DIOB hepatotoxicity from the onset of protein modification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 – 8 Recently, exposure to Dioscorea bulbifera L., a widely used herbal medicine was reported to display hepatotoxicities in human and experimental animals. 9 , 10 The main toxic ingredients were found to be diosbulbin B (DIOB) and 8‑Epidiosbulbin E Acetate (EEA), which both can be metabolized to the cis -enedial intermediate, and the liver injury correlated with the reaction of these electrophilic intermediates with cell protein. 11 – 13 Obviously, metabolic activation often plays a significantly critical role in the pathogenesis of the observed toxicities induced by drugs.…”
Section: Introductionmentioning
confidence: 99%